2017
DOI: 10.4081/jbr.2017.6254
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared conformational investigation of type I collagen aged by in vitro induced dehydration and non-enzymatic glycation treatments

Abstract: The two main ageing-inducing events in the collagenous tissues are the water loss and the formation of intermolecular crosslinks based on the reaction of collagen with matrix carbohydrates, following a mechanism known as non-enzymatic-glycation. With the aim to mimic the two deleterious processes for the protein structure, rat-tail collagen was submitted to hydration changes and allowed to interact with two sugars characterized by different reducing properties, D-glucose and D-ribose. Fourier transform infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Moreover, it has also been reported that aging affects the amide I to amide II ratio, as seen in Fig. 2c, lowering the signal of amide II and increasing of the signals in the 1100-1000 cm −1 spectral region, as a consequence of the formation of AGEs (Advanced Glycation Endproducts) 31 . Clearly, aging and signal artifact due to the sampling geometry affected the spectral quality and peak position.…”
Section: Resultsmentioning
confidence: 64%
“…Moreover, it has also been reported that aging affects the amide I to amide II ratio, as seen in Fig. 2c, lowering the signal of amide II and increasing of the signals in the 1100-1000 cm −1 spectral region, as a consequence of the formation of AGEs (Advanced Glycation Endproducts) 31 . Clearly, aging and signal artifact due to the sampling geometry affected the spectral quality and peak position.…”
Section: Resultsmentioning
confidence: 64%
“…Similar extracellular matrix compositional changes (higher AGEs and cross-linking) and lower bound water were observed alongside lower fracture resistance in aged (24 mo) male Fischer F344 rats ( Uppuganti et al, 2016 ). As a result of these and other works ( Bridelli et al, 2017 ; Jazini et al, 2012 ), it is hypothesized that loss of bound water and increased glycation are related and consequential steps during aging. While it is not entirely clear, evidence supports a loss of bound water may initiate glycation events ( Bridelli et al, 2017 ) while increased cross-linking may physically displace existing or prevent new bound water ( Kopp et al, 1989 ).…”
Section: Bone Water With Age and Diseasementioning
confidence: 83%
“…Indeed, glycated proteins showed higher absorption near the peak located at 3400 cm −1 . Previous studies also identified the presence of a shoulder near the peak at 3400 cm −1 when glycation occurred (Bridelli et al ., 2017). Moreover, it was pointed out that the higher the shoulder values, the higher the glycation rate (Otero de Joshi et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%